Pengaruh Belanja Online Terhadap Kebiasaan Konsumsi Dan Pengelolaan Keuangan Mahasiswa Ekonomi Islam UIN Fatmawati Sukarno Bengkulu - putri, Prisilia Anggraini; B, Idwal; Stiawan, Evan (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
This research aims to examine the influence of online shopping on consumption habits and financial management of Islamic Economics students at UIN Fatmawati Sukarno Bengkulu.The method used is quantitative with primary data through questionnaires distributed to 155 respondents. The results of path analysis show that online shopping has a significant effect on consumption habits with a coefficient of 0.39 and a significance of 0.000. but it has no significant effect on financial management with a coefficient of 0.027 and a significance of 0.807. Meanwhile, consumption habits have a significant effect on financial management with a coefficient of 0.493 and a significance of 0.000. So the Sobel test shows that consumption habits mediate the influence of online shopping on financial management with a z value of 2.052, which is greater than 1.96.